Scientific and Pedagogical Community in Russian Universities in the Context of the Program «Priority-2030» Implementation: Problems and Prospects - P. A. Ambarova; G. E. Zborovsky (Высшее образование в России, 2022)
The article presents a sociological view on the current problems of the scientific and pedagogical community (SPC) of universities participating in the strategic academic leadership program «Priority-2030». The main attention is paid to the characteristics of the trends in the development of the SPC, its contradictions and the possibilities of overcoming them. A special place is given to the sociological analysis of university management as a factor of scientific productivity of the SPC. The interaction of the SPC and university management is considered in the context of the goals of the Priority- 2030 program. The necessity of developing and implementation new principles of human capital management of SPC into university practices is substantiated. Among them are a differentiated approach to assessing the scientific activity of individual groups of SPCs; flexible restructuring of the main types of their professional activities; ensuring the high status of SPCs demonstrating major scientific achievements; overcoming anomalies and imitations in the activities of SPCs. The empirical basis of the article is the results of interviews with representatives of the SPC, analysis of documents, statistical data reflecting the development of Russian higher education in the XXI century.